Communication Strategies of Sumatran Students in Facing Culture Shock at UIN Sunan Kalijaga Yogyakarta - Nurhidayani, Nurhidayani (Dinasti Publisher, 2025)
This research discusses the communication strategies of students from Sumatra in facing culture shock at Sunan Kalijaga State Islamic University Yogyakarta. Differences in culture, language, and social norms between their hometown and the new environment often cause confusion and anxiety for migrant students. This study uses a qualitative method, with primary data from interviews and observations, and secondary data from supporting documents. The results show that the students adaptation process goes through four main stages: the honeymoon phase (feeling excited and happy in the new environment), the culture shock phase, the recovery phase (starting to open up, understand the culture, and build relationships), and the adjustment phase (being able to accept and feel comfortable with the local culture). The communication strategies used by the students include choosing the right messages according to the Javanese cultural context, adjusting their communication style to be more polite, and joining communities as a form of social support. In addition, the study found that culture shock affects three aspects: affective (emotions) such as confusion, anxiety, and sadness, behavioral, such as efforts to learn local habits and cognitive, such as changes in thinking patterns caused by differences in language and values. Even though it was full of challenges, Sumatra students were able to develop effective communication strategies, which helped them adapt and live their academic and social life better in Yogyakarta